ZINE SEBAGAI REPRESENTASI BUDAYA PERKOTAAN DI JAKARTA - Purnama Putra, Dhika (Kartala, 2022)
The study of zines as a representation of urban culture is seen from the application of its layout design. Zines in the context of urban culture have a complex relationship with the social dynamics of humans and their groups. As a product of today's subculture, Zine adapts to a particular segmentation based on the values espoused by zine makers and their communities. Zines will always evolve following their parent culture born from a particular subculture community. In the absence of standard rules regarding the format and practice, Zine will always develop following the dynamism of the subcutaneous urban community. This research is qualitative descriptive research with a layout design analysis approach which is then done reading the context and discussing the visual content of zines and seeing the meaning contained using Roland Barthes theory of visual semiotics. With this analysis, the study tried to un urban culture through Zines in cultural studies. The problem to be solved in this paper is how urban culture affects layout design in Zines as a representation of urban culture. In this study it was revealed that the relationship of cities and Zines is interrelated in the process of forming and forming. Cities can form Zines and vice versa. The study looked at Zines as a representation of urban culture.